A Review on Minimal Processing of Fruits and Vegetables - Wasana W.L.N.; Kariyawasam, H.K.P.P. (My University, 2020)
Even though food industry employs various processing and preservation methods still there is an enormous peak season postharvest loss of fruits and vegetables. Minimal processing is a very effective method of minimizing postharvest loss at a lower cost. Peeled and sliced fruits and vegetables, cleaned and packed leafy vegetables are some of popular minimally processed products. Cleaning, pealing, slicing, shredding, cooling and modified atmospheric packaging are some of common processes in this industry. Controlling ethylene production and respiration, maintaining proper sanitary conditions, best suited packaging and proper storage are the key factors affecting quality and shelf life of the products as increased respiration and ethylene production, enzymatic browning, increased microbial susceptibility are the main challenges of the industry. Freshness and ease of preparation are the most preferable qualities of these products which has led to its popularity. This review includes a summary of key physiological changes of minimally processed fruits and vegetables and some modern processing techniques used in industry to improve quality and shelf life of minimally processed products.
Keywords: Fruits and vegetables processing; Advances in minimal processing; physiology of minimal processed products; Natural sanitizers; Modified atmospheric packaging